Empowering students to enhance environmental awareness and foster ecopreneurship at SD Negeri 52 Pangkalpinang - Randi Syafutra; Sisi Pitriyana; Zakia Ayu Lestari (Community Empowerment, 2024)
The Community Service (CS) aims to empower students at SD Negeri 52 Pangkalpinang to enhance environmental awareness and foster ecopreneurship through environmental conservation education and practical skills. This CS encompasses 16 activities conducted from August 30th, 2024, to October 18th, 2024, involving 30 students from class V as participants. The results show that environmental conservation education and hands-on practice improved students' understanding, skills, and awareness of the importance of protecting the environment. Activities such as inorganic waste sorting and depositing selected waste at the waste bank, seedling tree planting, and placing succulents in classrooms effectively cultivated environmentally conscious behaviors among students. Furthermore, ecopreneurship training through the creation of eco-friendly products encouraged students to explore the economic potential of sustainable practices. With these outcomes, this CS is expected to impact the school and surrounding community and prepare students as a generation responsible for environmental sustainability.